Attitudes Toward Deliberate Self-Injury and Elective Cosmetic Surgery Patients in Emergency Department and Urgent Care Settings - Marion, Amber (My University, 2012)
Since 2003, the general acceptance of plastic surgery among all Americans surpassed 50% (American Society for Aesthetic Plastic Surgery, 2003). Additionally, deliberate self-injury (e.g., cutting), which is non-suicidal by nature, is a growing problem. Infection is a potential risk of both deliberate self-injury and elective cosmetic surgery (Mayo Foundation for Medical Education and Research, 2012). Prior research has shown attitudes and expectations for care differ among health care professionals for elective cosmetic surgery (ECS) and deliberate self-injury (DSI) patients, which can directly impact quality of care (Mackay and Barrowclough, 2005; Cooper, 2007). According to Weiner's (1986) Attributional Model of Helping Behavior, how people perceive and react to negative events occurring in the lives of others is influenced by attributions of control, locus (internal/external), and stability (likelihood of continuing). These attributions influence feelings, and the emotional reactions impact behaviors, including willingness to help. This study aimed to evaluate whether the primary attributions of Weiner's model relate to differential attitudes towards deliberate self-injury (DSI) and elective cosmetic surgery (ECS) patients seeking care for an infection in an emergency department or urgent care setting. This study was designed to test the hypothesis that medical staff will attribute greater control, internal locus, and stability to a patient presenting with an injury due to DSI than they will attribute to a patient presenting with an ECS post-operation injury. These attributions will negatively impact their attitudes, and consequently their willingness to help the patient.
Color poster with text, charts, and graphs.
Keywords: Medical personnel--Attitudes; Self mutilation; Surgery, Elective; Hospitals--Emergency service; Posters